Penyuluhan Kesehatan Memanfaatkan Tumbuhan Obat Tradisional Warisan Leluhur Untuk Kesehatan Masa Kini Di Kelurahan Padaleu Kecamatan Kambu Kota Kendari Sulawesi Tenggara - La Aso; Wa Ode Sifatu; Elsa Septiani Putri; Lilik Rita Lindayani; Laxmi, Laxmi; Ardila; Ni Luh (Jurnal Pengabdian, 2025)
The objective of PKM (Community Service) is to increase public knowledge about selecting plants for treating certain diseases at home and how to use them, as well as to create health independence in the community. In addition, this activity aims to raise public awareness of the importance of utilizing local plants as traditional medicines inherited from ancestors, especially in Padaleu Village. The materials used in this activity included knowledge about the management of plants for traditional medicine and public health, as well as anthropology and health materials from competent sources. The methods used were lectures and discussions to improve the competence and understanding of the community, especially housewives and local government officials. This activity was carried out directly through counseling and question and answer sessions so that participants could understand and apply this knowledge in their environment. The results of the study show that the outreach activity succeeded in increasing the knowledge and awareness of the community, especially housewives and Dasawisma administrators, about the use of local plants as traditional medicine inherited from their ancestors. Participants showed great enthusiasm and actively asked questions about traditional medicine and its use. In addition, this activity was able to create a more independent community in managing health and utilizing natural resources in a sustainable manner. The conclusion of this report is that educational activities on the use of local plants as traditional medicine have successfully increased the knowledge, attitudes, and skills of the community, especially housewives and Dasawisma administrators, in managing and utilizing plants for family health. In addition, these activities are expected to encourage community health independence and preserve local wisdom related to traditional medicine inherited from ancestors.